ANALISIS KAIDAH NAHWU DALAM BAHASA ARAB DI GAME ONLINE MOBILE LEGENDS - Suharsono; Dian Arista; Munirul Abidin (Matluba: Jurnal Pendidikan Bahasa dan Budaya Arab, 2023)
Mobile legends is one of the most popular Multiplayer Online Battle Arena (MOBA) games in Indonesia. In one match, there are 10 players divided into two teams, namely 5 blue teams and 5 red teams. The main target of this game is the tower in the three lanes and the main tower. One of the teams that can destroy the enemy's main tower first, he is the one who wins. In this game, there are various kinds of heroes with their respective characters. In addition, there are various interesting features in this game, one of which is language. There are 4 kinds of languages provided in this game, namely Indonesian, Japanese, English, and Arabic. The Arabic language used is Fushah Arabic. This is something interesting for the author to examine whether the Arabic used in the mobile legends game which incidentally uses the system, is in accordance with the existing nahwu rules or not.